Short-segment decompression/fusion versus long-segment decompression/fusion and osteotomy for Lenke-Silva type VI adult degenerative scoliosis - Hao-Cong Zhang; Hai-Long Yu; Hui-Feng Yang; Peng-Fei Sun; Hao-Tian Wu; Yang Zhan; Zheng Wang; Liang-Bi Xiang; Xin Chen (Chinese Medical Journal, 2019)
Abstract. Background:. The effect of short-segment decompression/fusion versus long-segment decompression/fusion and osteotomy for Lenke-Silva type VI adult degenerative scoliosis (ADS) has not been clarified. This study aimed to compare the clinical and radiographic results of short-segment fusion vs. long-segment fusion and osteotomy for patients with Lenke-Silva type VI ADS. Methods:. Data of 28 patients who underwent spinal surgery for ADS from January 2012 to January 2014 in the General Hospital of Northern Theater Command were reviewed. Of the 28 patients, 12 received long-segment fusion and osteotomy and 16 received short-segment fusion. Radiographic imaging parameters and clinical outcomes, including the sagittal vertical axis (SVA), lumbar lordosis (LL) angle, pelvic tilt (PT), sacral slope (SS), the visual analog scale (VAS), Japanese Orthopedic Association (JOA), Oswestry disability index (ODI), and lumbar stiffness disability index (LSDI) scores, were recorded. The difference between groups was compared using the dependent t test or Chi-squared test. Results:. The Cobb and LL angles and SVA improved in both groups; however, PT and SS angles did not improve following short fusion. There were significant differences in the post-operative SVA (26.8 ± 5.4 mm vs. 47.5 ± 7.6 mm, t = –8.066, P < 0.001), PT (14.7 ± 1.8° vs. 29.1 ± 3.4°, t = –13.277, P < 0.001), and SS (39.8 ± 7.2° vs. 26.1 ± 3.3°, t = 6.175, P < 0.001) between the long and short fusion groups. All patients had improved ODI, JOA, and VAS scores post-operatively (all P < 0.001), with no significant difference between the groups (all P > 0.05). The post-operative LSDI score was 3.5 ± 0.5 in the long fusion group, which was significantly higher than that of the short fusion group (1.4 ± 0.7; P < 0.001). Conclusions:. The clinical outcomes of patients with Lenke-Silva type VI ADS who underwent short-segment decompression/fusion were comparable to those of patients who underwent long-segment decompression/fusion and osteotomy despite poor correction of sagittal imbalance. Moreover, short-segment decompression/fusion showed a short operation time and reduced surgical trauma.